Letters, Notes, & Comments - Mackler, Aaron L. (Journal of religious ethics, 1999)
Comment by Aaron L. Mackler on “‘Through Her I Too Shall Bear a Child’: Birth Surrogates in Jewish Law” by Elie Spitz Reply by Elie Kaplan Spitz Research Note by G. Scott Davis